Sintilimab combined with axitinib in the treatment of advanced chromophobe renal cell carcinoma: a case report - Zhang, Huimin; Cong, Xiaofeng; Chen, Chen; Liu, Ziling (Frontiers in Oncology, 2024)
Chromophobe renal cell carcinoma (ChRCC) is a rare pathological type of renal cell carcinoma (RCC). Related systematic studies involving large numbers of patients are lacking, and more importantly, there is currently no international consensus on post-line treatment guidelines for ChRCC. The rapid development of systemic treatment with molecular targeted therapies and immune checkpoint inhibitors has brought effective approaches for patients with clear cell renal cell carcinoma (ccRCC), while progress in the treatment of ChRCC is still limited. In this case report, the patient was initially diagnosed at the early stage; 4 years post-surgery, she developed lung metastases and the disease progressed once again after being treated with sunitinib monotherapy for 3 years. However, after combining the immunotherapy sintilimab with the targeted therapy axitinib as second-line treatment, imageological examination showed lesions in the lungs that gradually decreased, and the bone metastases remained stable. To date, the patient has been continuously treated for over 2 years and is still undergoing regular treatment and follow-up. This case is the first to report the long-term survival of metastatic disease by using this treatment regimen and to propose a potential therapeutic option for patients with metastatic ChRCC. Since only one case was observed in this report, further study is needed.